Assessing Colistin Resistance by Phenotypic and Molecular Methods in Carbapenem-resistant Enterobacterales in a Tertiary Care Hospital in Pakistan - Furqan W; Ali S; Usman J; Hanif F; Naeem A; Nasrullah A; Tayyab N (Infection and Drug Resistance, 2022)
Warda Furqan, Sakhawat Ali, Javaid Usman, Faisal Hanif, Afnan Naeem, Amnah Nasrullah, Nadia Tayyab Department of Microbiology Army Medical College (National University of Medical Sciences), Rawalpindi, PakistanCorrespondence: Warda Furqan, House No. 4, Street No.18, Sector H DHA2, Islamabad, Pakistan, Tel +92-336-5141818, Email warda_khan28@yahoo.comIntroduction: Members of Enterobacterales are very common pathogens, which continue to show resistance to many antibiotics. Carbapenem performed well for some time. Colistin was the final hope for the carbapenem-resistant Enterobacterales, but resistance against it has virtually tied the clinician’s hands, especially when it comes to treating critically ill patients.Purpose: Detection of colistin resistance by the agar method as well as by the polymerase chain reaction (mobilized colistin resistance-1 gene) in carbapenem-resistant Enterobacterales.Materials and Methods: A cross-sectional study from Dec 2019 to Dec 2020 was conducted at the Department of Microbiology, Army Medical College, National University of Medical Sciences Rawalpindi Pakistan. Antimicrobial susceptibility of Enterobacterales was determined according to the Kirby–Bauer disc diffusion method except for colistin. Colistin agar was used, in concentrations of 2 μg/mL and 4 μg/mL. Results were interpreted according to Clinical and Laboratory Standards Institute guidelines 2020. Mobilized colistin-resistant-1 gene in the carbapenem resistant Enterobacterales was detected by performing real-time polymerase chain reaction assay.Results: Among the 172 carbapenem-resistant Enterobacterales 18 isolates were resistant using the colistin agar test. Whereas by molecular method colistin resistance was detected among 10 isolates that carried mobilized colistin resistance 1 gene, making the frequency of the MCR-1 gene 5.81%. Seventy percent of isolates were from paired blood samples. Eight patients, from whom the colistin resistant gene was isolated expired.Conclusion: Colistin resistance is a very serious issue and should not be missed in a clinical microbiology laboratory. The phenotypic agar test method is an excellent option for routine use, as it combines ease of performance with affordable cost. However, molecular methods are essential for the detection of mobilized colistin resistance gene (1– 9) for epidemiological purposes.Keywords: carbapenem-resistant Enterobacterales, colistin agar test, Enterobacterales, mobilized colistin resistant-1 gene, phenotypic method, real time polymerase chain reaction